Genetic Mapping of Major‐Effect Seed Dormancy Quantitative Trait Loci on Chromosome 2B using Recombinant Substitution Lines in Tetraploid Wheat. Issue 1 (1st January 2016) - Chao, Shiaoman; Elias, Elias; Benscher, David; Ishikawa, Goro; Huang, Yung‐Fen; Saito, Mika; Nakamura, Toshiki; Xu, Steven; Faris, Justin; Sorrells, Mark
ABSTRACT: Durum wheat ( Triticum turgidum L.) cultivars can benefit from having some level of seed dormancy to help reduce seed damage and lower grain quality caused by preharvest sprouting (PHS) occurring during wet harvesting conditions. Previously, a single chromosome substitution line carrying chromosome 2B of wild emmer [ Triticum turgidum L. subsp. dicoccoides (Körn. ex Asch. & Graebn.) Thell.] in the durum cultivar Langdon background was found to have higher levels of seed dormancy and PHS tolerance. In this study, a population of recombinant substitution lines was developed and used to construct a single nucleotide polymorphism (SNP)‐based high‐density genetic linkage map. Seed germination tests were used to evaluate seed dormancy levels. Multiple interval mapping analysis revealed four quantitative trait loci (QTL) regions affecting seed dormancy. Two regions containing major‐effect QTL contributed by wild emmer were consistently expressed in four environments and explained 5.89 to 11.14% of the phenotypic variation. One QTL region was located near the centromere and the other on the long arm of chromosome 2B in Bayes credible intervals of 4 and 7 cM, respectively. Recombinant inbred lines (RILs) carrying both QTL had an average of 35% reduced rate of germination measured by weighted germination index compared with RILs carrying neither QTL. The two QTL regions identified in this study should be useful for improving PHS tolerance in wheat. Efforts to transfer the two QTL into elite durum cultivars are in progress to examine the effects of genetic background and environment on QTL expression and to evaluate the performance of other agronomic traits in the presence of the QTL.